Spring fattening in non-migratory female Greylag Geese Anser anser regardless of social status - Ehret, Simone A. A.; Berthoud, Jean-Louis; Woog, Friederike (Wildfowl, 2020)
Geese vary their body mass throughout the annual cycle. Before energy demanding processes such as migration, breeding and moult, they accumulate fat reserves, mainly in their abdomen. Females in particular may face a nutritional bottleneck during spring, when they produce and incubate eggs. Clutch size and thus reproductive success is positively linked to female body condition and ultimately evolutionary fitness. Using a marked flock of resident Greylag Geese Anser anser in southwest Germany, where only c. 12% of the local birds breed (according to 2016 data), we showed that female geese put on weight regardless of their breeding or social status, but males did not. Even unpaired females with no breeding opportunity in the coming season gained weight, taking advantage of the ample feeding opportunities. This strongly suggests an underlying endogenous process of spring fattening in female Greylag Geese.